2012
DOI: 10.1002/14651858.cd006251.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to prevent injuries in construction workers

Abstract: Background Construction workers are frequently exposed to various types of injury-inducing hazards. A number of injury prevention interventions have been proposed, yet their effectiveness is uncertain. Objectives To assess the effects of interventions to prevent injuries in construction workers. Search methods We searched the Cochrane Injuries Group's specialised register, CENTRAL, MEDLINE, EMBASE, PsycINFO, OSH-ROM (including NIOSHTIC and HSELINE), Scopus, Web of Science and EI Compendex to September 2011. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 50 publications
2
34
1
Order By: Relevance
“…However, in terms of successful interventions to prevent fatal injuries in construction sites, a recent review (van der Molen et al, 2012) concluded that regulation, training, inspections, and occupational health services are ineffective. Safety culture has also struggled to establish itself as a research topic in construction, emerging later than in other industries and declining since 2008 (Zhou et al, 2015).…”
Section: Figure 1 -A Timeline Illustrating the Ages Of Safety Based Onmentioning
confidence: 99%
“…However, in terms of successful interventions to prevent fatal injuries in construction sites, a recent review (van der Molen et al, 2012) concluded that regulation, training, inspections, and occupational health services are ineffective. Safety culture has also struggled to establish itself as a research topic in construction, emerging later than in other industries and declining since 2008 (Zhou et al, 2015).…”
Section: Figure 1 -A Timeline Illustrating the Ages Of Safety Based Onmentioning
confidence: 99%
“…van der Molen et al 2012;Leider et al 2015;Chang et al 2016). We hope to be publishing papers that build the evidence base for ergonomics interventions: high quality studies, prospective rather than cross-sectional designs and robust sample sizes.…”
Section: Authors Titlementioning
confidence: 99%
“…The remaining interventions were effective but poor methodological quality and significant heterogeneity meant that the means by which these interventions changed behaviour was unclear. In an updated review in 2012 (13 studies; van der Molen et al, 2012), it was similarly concluded that there was no evidence that the introduction of safety legislation/regulations alone or that regionally-oriented interventions such as inspections or training were effective in reducing injuries. There was, however, low-level evidence that company-oriented interventions (e.g., multifaceted safety campaign, drug-free workplace) resulted in reduced injuries (van der Molen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In an updated review in 2012 (13 studies; van der Molen et al, 2012), it was similarly concluded that there was no evidence that the introduction of safety legislation/regulations alone or that regionally-oriented interventions such as inspections or training were effective in reducing injuries. There was, however, low-level evidence that company-oriented interventions (e.g., multifaceted safety campaign, drug-free workplace) resulted in reduced injuries (van der Molen et al, 2012). Another review of three interventions specifically to reduce falls in the construction industry also found limited evidence for effectiveness (Rivara and Thompson, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation